2018
DOI: 10.1186/s11671-018-2471-z
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into CO2 Adsorption on Layered Double Hydroxide (LDH)-Based Nanomaterials

Abstract: The interlamellar spacing of layered double hydroxides (LDHs) was enlarged by dodecyl sulfonate ions firstly, and then, (3-aminopropyl)triethoxysilane (APS) was chemically grafted (APS/LDHs). The structural characteristics and thermal stability of these prepared samples were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), reflectance Fourier transform infrared spectrometer (FTIR), thermogravimetric analysis (TG), and elemental analysis (EA) respectively. The CO2 adsorption per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…[ 2 ] There are also indications that some gas species can be captured by the anions in the galleries. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 ] There are also indications that some gas species can be captured by the anions in the galleries. [ 28 ]…”
Section: Resultsmentioning
confidence: 99%
“…Then, a novel approach where a monolayer of terminal amino groups of APS is grafted onto LDHs (APS/LDHs) for CO 2 capture was explored by Tang et al 70 It was found that the enlarged layer spacing pillared by dodecyl sulfonate is beneficial to APS introduction. APS is tethered to the LDH laminates through covalent interaction.…”
Section: The Fundamentals For Co2 Photoreductionmentioning
confidence: 99%
“…[ 185 ] LDHs are a promising layered material in the field of photocatalytic CO 2 RR emerged from their high adsorption capacity (0.5–1.4 mmol g sorbent −1 ), [ 186 ] which is attributed to the abundance of OH − groups [25a,187] that function to facilitate the reduction of CO 2 on the active sites. [ 188 ] Table 8 presents a summary of 2D LDH compounds studied in the field of light‐driven CO 2 RR.…”
Section: Applications Of Ldh‐based Photocatalysts For Artificial Photosynthesismentioning
confidence: 99%